Psychological first aid for Ukrainian civilians: protocol and reflections on a volunteer international phone-based intervention - Shraga, Yanina; Pushkarskaya, Helen; Sarid, Orly (Frontiers in Digital Health, 2025)
Informal mental healthcare groups often provide telephonic and text-based interventions to support communities affected by natural and man-made disasters. Operating outside formal regulations, these groups offer flexible and innovative care; documenting their practices is crucial for evaluating service quality. This paper presents a protocol of an international, informal Psychological First Aid (PFA) telephone-based initiative and a reflective account from a volunteering therapist. The initiative aimed to support Ukrainian civilians affected by the Russian-Ukrainian war through crisis intervention and resilience-building. Guided by PFA principles, theoretical first aid models, and evidence-based practices, the telephone interventions focused on reducing distress, providing moral support, and restoring functioning. A Russian-speaking therapist assisted 34 Ukrainian civilians, primarily addressing acute stress, anxiety, and panic attacks. Using an autoethnographic approach, this study integrates the therapist's retrospective reflections, cultural context, and professional learning to examine PFA implementation in a crisis setting. Individuals who received telephone-based PFA reported decreased distress and enhanced coping strategies, suggesting effectiveness. The initiative's three-year continuation illustrates its sustainability. The therapist's reflections highlight the importance of professional preparation, shared linguistic and cultural backgrounds, and a sense of purpose in delivering effective support. While limitations include the absence of standardized measures and potential self-selection and volunteer biases, this study demonstrates the feasibility of providing remote psychological first aid to civilians through informal international groups. Critically evaluating practices adopted by these informal organizations is essential for understanding their effectiveness, improving future implementation, and co-creating best practices for crisis intervention and support services that embrace “Care Without Address” models.